Kajian Numerik Ketebalan Lapisan Redaman Getaran Berbahan Semen untuk Dek Kapal Penumpang - Wibowo H Nugroho; Nanang J H Purnomo; Endah Suwarni (Universitas Muhammadiyah Sidoarjo, 2016)
Ship vibration problems today's increasingly complex and often occurs in addition to the strict requirements of ship classification agencies for allowable levels of vibration so that passengers and crew more comfortable and secure. One method for reducing the influence of ship structural vibration is to minimize the response of the vibration by using damper. This paper describes the effect of the thickness of the damping layer made from cement material on the deck plate due to the harmonic load excitation. As cement is a common damper application on the ship deck. A numerical modeling based on finite element analysis was applied in two-layer conditions, namely an overall and tiling coating. The results of this study indicate that thee minimum thickness of the cement layer has an optimum damping for the overall coating is approximately 8 mm and as for tile coating is approximately 15 mm.